Effects of a newly developed potent orexin-2 receptor-selective antagonist, compound 1 m, on sleep/wakefulness states in mice - Etori, Keishi; Saito, Yuki; Tsujino, Natsuko; Sakurai, Takeshi (Frontiers in Neuroscience, 2014)
Orexins (also known as hypocretins) play critical roles in the regulation of sleep/wakefulness states by activating two G-protein coupled receptors (GPCRs), orexin 1 (OX1R) and orexin 2 receptors (OX2R). In order to understand the differential contribution of both receptors in regulating sleep/wakefulness states we compared the pharmacological effects of a newly developed OX2R antagonist (2-SORA), Compound 1 m (C1 m), with those of a dual orexin receptor antagonist (DORA), suvorexant, in C57BL/6J mice. After oral administration in the dark period, both C1m and suvorexant decreased wakefulness time with similar efficacy in a dose-dependent manner. While C1m primarily increased total non-rapid eye movement (NREM) sleep time without affecting episode durations and with minimal effects on REM sleep, suvorexant increased both total NREM and REM sleep time and episode durations with predominant effects on REM sleep. Fos-immunostaining showed that both compounds affected the activities of arousal-related neurons with different patterns. The number of Fos-IR noradrenergic neurons in the locus coeruleus was lower in the suvorexant group as compared with the control and C1m-treated groups. In contrast, the numbers of Fos-IR neurons in histaminergic neurons in the tuberomamillary nucleus and serotonergic neurons in the dorsal raphe were reduced to a similar extent in the suvorexant and C1m groups as compared with the vehicle-treated group. Together, these results suggest that an orexin-mediated suppression of REM sleep via potential activation of OX1Rs in the locus coeruleus may possibly contribute to the differential effects on sleep/wakefulness exerted by a DORA as compared to a 2-SORA.